THE ROLE AND IMPORTANCE OF ARTIFICIAL INTELLIGENCE IN LEARNING FOREIGN LANGUAGES (American Journal of Technology and Applied Sciences, 2024)
Artificial intelligence is one of the most important and interesting fields of modern technologies, which is causing revolutionary changes in various aspects of human life, including education and learning foreign languages. Today, the process of learning foreign languages, in addition to traditional methods, is becoming more effective and interesting through the use of artificial intelligence technologies. This article provides a detailed analysis of the role and importance of artificial intelligence in foreign language learning, as well as information on how to create opportunities to improve this process.